Multi‐Trait Polygenic Risk Score, Nongenetic Determinants, and Cardiovascular Disease Death: A Cohort Study of 14 086 Japanese Individuals - Ryosuke Fujii; Mako Nagayoshi; Masahiro Nakatochi; Shuntaro Sato; Yoshiki Tsuboi; Koji Suzuki; Hiroaki Ikezaki; Yuichiro Nishida; Yoko Kubo; Shiroh Tanoue; Sadao Suzuki; Teruhide Koyama; et al. (Journal of the American Heart Association: Cardiovascular and Cerebrovascular Disease)
Background Although utility of composite trait‐specific polygenic risk score (multi‐trait PRS) has been examined among European ancestries, few studies investigated among East Asians and incorporated modifiable risk factors. We examined the associations of multi‐trait PRS for cardiometabolic factors with cardiovascular disease mortality by integrating nongenetic determinants. Methods A total of 14 086 Japanese participants (mean age, 55±9; 55.8% women) of the J‐MICC (Japan Multi‐Institutional Collaborative Cohort) study were analyzed in this study. We calculated 6 PRSs for cardiometabolic traits (systolic blood pressure, body mass index, triglycerides, low‐density lipoprotein cholesterol, estimated glomerular filtration rate, and hemoglobin A1c). Based on these PRSs, we developed multi‐trait PRS and considered as a primary exposure. Three nongenetic factors (smoking, alcohol drinking, and educational attainment) from the self‐reported questionnaire were also examined. Results During a median 12.1‐year follow‐up period, a total of 472 all‐cause and 79 cardiovascular disease mortality cases were documented. Compared with 0% to 90% of multi‐trait PRSs, an adjusted hazard ratio (HR) among the top 10% of multi‐trait PRSs was 1.32 (95% CI, 1.00–1.73) for all‐cause death and 2.63 (95% CI, 1.48–4.67) for cardiovascular disease death. Incorporation of educational attainment with multi‐trait PRSs showed null associations in those who went beyond high school (HR, 2.07 [95% CI, 0.44–9.66]) even in the top 10% of multi‐trait PRS. Conclusions Our analysis combining both genetic and nongenetic determinants highlighted that lifestyle factors and educational attainment can slightly reduce an individual's composite genetic risk for cardiovascular disease death.